Relationship between Innovation Management and Innovative Organizational Culture in Logistics Companies: A Study in the City of Mersin - Bekir Çağlar Bayhan; Oya Korkmaz (Istanbul Business Research (IBR), 2021)
Innovation management is essential for the growth and success of an organization. Innovation management is a precursor to the establishment of an innovative organizational culture. By encouraging staff to engage in innovative behavior, innovation management facilitates the creation and establishment of a culture of innovation in an organization. An organization can only change its cultural attitude and behavior by investing in innovation management practices—i.e., by applying innovation to the organization's strategies, systems, and procedures. To effectively establish an innovative culture, organizations should continuously implement innovation management practices. Only in this way can innovation become an organization's dominant culture. Because innovation management practices increase the commitment to innovation, they facilitate the formation and development of an innovative organizational culture and eventually become the fundamental values of the organization. In this study, we posited that innovation management constitutes the basis for the formation of an innovative organizational culture and analyzed this hypothesized relationship. For this purpose, we collected data using the face-to-face survey method with 200 white-collar staff members working in logistics companies that operate in Mersin, Turkey and that apply innovative management practices. We assessed the collected data using SPSS 20.0 (Statistical Package for Social Sciences) and AMOS 24.0 (Analysis of Moment Structures) programs. Our analysis showed a highly significant positive relationship between innovation management and innovative organizational culture.
Keywords: 650; Innovation Management; Innovative Organizational Culture; Logistics